Principals’ Leadership Styles And Job Performance Of Teachers In Public Secondary Schools In Imo State, Nigeria - Obi, Chidinma Evan; Onyeike, Victoria C. (Archives of Business Research, 2018)
The study investigated the extent principals’ leadership styles predict job performance of teachers in public secondary schools in Imo State. Four research questions were answered while four hypotheses were tested at 0.05 alpha level. The study adopted a correlational research design. The population for this study comprised all the four hundred and thirty (430) vice principals in the public secondary schools spread across the six (6) educational zones in Imo State. A sample of 239 vice principals were drawn with the use of multi-stage sampling approach. Two sets of instruments titled Principals’ Leadership Styles Questionnaire (PLSQ), and Job Performance of Teachers (JPTQ) were used and duly validated. The Cronbach alpha was used to compute the reliability coefficients of the instruments as follows: Principals’ Leadership Styles Questionnaire (PLSQ) - 0.720, and Job Performance of Teachers Questionnaire (JPTQ) - 0.720. Data were analyzed using multiple and simple regression, which were used to answer the research questions, while ANOVA associated with multiple regressions and t-test associated with simple regression respectively were used to test the null hypotheses. The result of the study revealed that principals’ leadership styles jointly and significantly predicted job performance of teachers in secondary schools in Imo State. Transformational leadership style was the most potent predictor of job performance. It was recommended among others that school principals should endeavour to enroll in leadership training programmes from time to time in order to enhance their leadership quality and efficiency for improved job performance of teachers.